Transforming growth factor beta 1 polymorphisms and haplotypes associated with breast cancer susceptibility: A case-control study in Tunisian women - Hadj-Ahmed, Mariem; Ghali, Rabeb M; Bouaziz, Hanen; Habel, Azza; Stayoussef, Mouna; Ayedi, Mouna; Hachiche, Monia; Rahal, Khaled; Yacoubi-Loueslati, Besma; Almawi, Wassim Y (Tumor biology, 2019)
Variable association of transforming growth factor beta 1 (TGFβ1) in breast cancer (BC) pathogenesis was documented, and the contribution of specific TGFB1 polymorphisms to the progression of BC and associated features remains poorly understood. We investigated the contribution of TGFB1 rs1800469, rs1800470, rs1800471, and rs1800472 variants and 4-locus TGFB1 haplotypes on BC susceptibility, and pathological presentation of BC subtypes. Study subjects comprised 430 female BC cases, and 498 cancer-free control women. BC-associated pathological parameters were also evaluated for correlation with TGFB1 variants. Results obtained showed that the minor allele frequency (MAF) of rs1800471 (+74G>C) was higher seen in BC cases than in control subjects, and was associated with increased risk of BC. Significant differences in rs1800471 and rs1800469 (−509C>T) genotype distribution were noted between BC cases and controls, which persisted after controlling for key covariates. TGFB1 rs1800472 was positively, while rs1800470 was negatively associated with triple negativity, while rs1800470 positively correlated with menarche, but negatively with tumor size and molecular type, and rs1800469 correlated positively with menstrual irregularity, distant metastasis, nodal status, and hormonotherapy. Heterogeneity in LD pattern was noted between the tested TGFB1 variants. Four-locus (rs1800472-rs1800471-rs1800470-rs1800469) Haploview analysis identified haplotype TGCT to be negatively associated, and haplotypes CGTT and CCCC to be positively associated with BC. This association of CGTT and CCCC, but not TGCT, with BC remained significant after controlling for key covariates. In conclusion, TGFB1 alleles and specific genotypes, and 4-locus TGFB1 haplotypes influence BC susceptibility, suggesting dual association imparted by specific SNP, consistent with dual role for TGFB1 in BC pathogenesis.